Efektivitas Program IISMA (Studi Kasus di Universitas Negeri Jakarta) - Habira Rusyda; Jenny Sista Siregar; Neneng Silfi Ambarwati (Journal on Education, 2025)
This research is done to evaluate the effectiveness of the international student exchange program IISMA at the State University of Jakarta. The construction of this study is done to see if the student mobility program is done effectively in the State University of Jakarta. The method used in the research is a qualitative approach with interview and observation as its research methods. The researcher chose a qualititative approach with qualitative methods because researcher want to observe and evaluate the effectiveness of the IISMA Program at the State University of Jakarta. Furthermore, the researcher collect the information using participatory as well as direct observation and interview as data collecting procedure. The result shows that the IISMA program at the State University of Jakarta hasn’t been effectively done. The result is determined from the inability to reach the program’s goals as its effectiveness indicator. This caused by external inhibitions in which there’s certain line of conditions that were not met that hindered the program’s goals to be reached.